Neuroarchitectural Design Element Implication on Student-Athlete School with Holistic Athlete Development - Muhamad Refi Fauzan Akbar; Iwan Sudradjat (SEAN Institute, 2026)
The physical and cultural environment we create influences our thinking, emotions, and behavior. Architecture plays a role in shaping us as humans, contributing to human well-being. Architecture is a built environment inhabited by humans and engaged in activities within it. Architectural manifestations are always rooted in the physical body, and architectural design has the capacity to nurture, stimulate, or even destroy these through the influences that emerge from/impact human perception patterns and experiences of the space. The International Olympic Committee recommends that youth athlete development programs focus on athletes' health, ability, and resilience, along with broad, inclusive, sustainable, and enjoyable achievement. The term